2020
DOI: 10.1007/s10853-020-04459-z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sorption capacity of crystal lattice defects and low Miller index surfaces of copper

Abstract: The effect of hydrogen on the physical-chemical properties of copper is directly dependent on the types of chemical bonding between H and lattice defects in Cu. In this work, we performed a systematic study of the bonding of H-atoms with crystal lattice defects of copper. This included three types of symmetric tilt grain boundaries (GBs), R3, R5 and R11, and the low Miller index surfaces, (111), (110) and (100). A comparison with literature data for the bonding of H-atoms with point defects such as vacancies w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 49 publications
3
18
1
Order By: Relevance
“…We have chosen this GB because it occurs frequently in fcc Cu [16][17][18] and it has a geometry with a diverse openness due to sites with different coordination numbers and local volume at the GB plane. In a previous work we have shown that the volume expansion is a key parameter for driving the segregation of dopants to GBs [1,7]. The GB model of Figure 1 was constructed using the coincidence-site lattice (CSL) method and a periodic supercell that contains two oppositely oriented Σ9 GBs.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…We have chosen this GB because it occurs frequently in fcc Cu [16][17][18] and it has a geometry with a diverse openness due to sites with different coordination numbers and local volume at the GB plane. In a previous work we have shown that the volume expansion is a key parameter for driving the segregation of dopants to GBs [1,7]. The GB model of Figure 1 was constructed using the coincidence-site lattice (CSL) method and a periodic supercell that contains two oppositely oriented Σ9 GBs.…”
Section: Figurementioning
confidence: 99%
“…We have shown previously that for fcc Cu the Σ5 and Σ11 GBs can increase the strength of the segregation of substitutional impurities at certain atomic sites while the Σ3 GB has no ability to trigger the segregation of impurities [7]. The dominating effect is the volume expansion at certain GB sites of the Σ5 and Σ11 and because the Σ3 has no sites with considerable volume expansion, the segregation of impurities from the bulk is not favorable [1,7].…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations